Poverty Does Make Us Sick - Nazim Habibov; Alena Auchynnikava; Rong Luo (Ubiquity Press, 2019)
This study evaluates the direct causal effects of household wealth on health. We discuss several specific mechanisms that that could relate poverty with worse health and hypothesize that poverty will undermine population health. This hypothesis was tested based on data drawn from a recent cross-country survey in 12 post-Soviet countries and Mongolia using classic regression (OLS) and instrumental variable 2SLS regressions. The results indicate that poverty does indeed lead to worsening health. This negative effect of poverty on health remains unchanged after controlling for a wide range of individual characteristics, healthcare performance indicators, trust in individuals, government, parliament, and political parties, as well as country-level unobserved characteristics. Using an instrumental variable increases our confidence in being able to isolate the effects of poverty on health status and confirms that our results are not due to endogeneity. In addition, the strong negative effect of poverty on health remains robust to the use of a set of country-level aggregated indicators (e.g. GDP and Gini) instead of country dummies, the employment of a subjective self-assessment indicator of poverty instead of an objective one, and an alternative conceptualization of health status as a binomial variable (for bad and very bad health) instead of a continuous one.